STRATEGIC THINKING: SOCIO-CULTURAL FRAMES AND CONTEXTS - Jarmoszko, Stanisław (The Copernicus Journal of Political Studies, 2020)
The aim of the article is to reconceptualize the term/phenomenon “strategic thinking”. First of all, it discusses socio-cultural roots and contexts of strategic thinking. Although strategic thinking rests on the neuro-psychical thinking mechanisms of an individual, it is a peculiar process as it is a competence mastered through practical and educational activities (in a specific socio-cultural context), which requires an appropriate conceptual-intellectual training. The article is of the viewpoint-conceptual nature. On the basis of the review and critical analysis of the theoretical interpretations of strategic thinking, the author of this article presents his own system of defining, structuring or enumerating the basic socio-cultural frames. The main result is the conceptualization of strategic thinking culture. Owing to the increasing worldwide significance of strategic thinking – in various areas of human activity – the considerations included in the article may considerably contribute to the progress of the universal theory of strategy. The content can facilitate the development of human perception of reality and their effective performance within the reality.